THE LEGAL BASIS OF SOIL PROTECTION AND EFFECTIVE USE WILL BE CREATED (Conference Zone, 2022)
Land is considered the main means of production in agriculture, and maintaining, protecting and effectively using soil fertility in adapting to global climate change, preventing soil salinization, erosion and eliminating its consequences is one of the most urgent global environmental problems facing the world community today.